Responses of Microcystis aeruginosa (Cyanobacteria) to sanguinarine stress: morphological and physiological characteristics associated with competitive advantage. Issue 3 (4th May 2019) - Lin, Yiqing; Chen, Anwei; He, Yaxian; Qing, Chun; Peng, Liang; Luo, Si; Shao, Jihai
ABSTRACT: Microcystis aeruginosa has several morphological and physiological traits that frequently enable it to dominate in eutrophic waters. Sanguinarine is a promising algaecide of biological origin that shows strong inhibitory effects against M. aeruginosa . The effects of sanguinarine on the morphological and physiological characteristics that give M. aeruginosa an ecologically competitive advantage over other phytoplankton were investigated in this study. The results showed that sanguinarine could effectively inhibit the growth of M. aeruginosa . Sanguinarine did not affect buoyancy regulation in M. aeruginosa but did increase colony size. Examination of intracellular and extracellular microcystin showed that although its synthesis was inhibited by sanguinarine, it recovered after 5 days of exposure at concentrations of 10 to 40 μg l −1 . Hormetic effects were observed for phycobiliprotein content and carbonic anhydrase (CA) activity under sanguinarine stress. Phosphorus (P) uptake by M. aeruginosa was inhibited by sanguinarine. The results presented in this study will help elucidate the ecological effects of sanguinarine when used to mitigate the effects of harmful cyanobacteria.